THE RELATIONSHIP BETWEEN THE INCIDENCE OF HYPERTENSION AND THE FULFILMENT OF REST AND SLEEP NEEDS IN THE ELDERLY IN BUAHDUA VILLAGE WEST JAVA - Fitri Septiandini, Puji; Purnama Hoedaya, Ahmad; Inriyana, Ria (Buletin Veteriner Udayana, 2024)
Hypertension is defined as a condition where a person has blood pressure above normal values (≥ 140/90 mmHg). One of the basic needs that is disturbed in hypertension sufferers is the need for rest and sleep. Poor sleep quality can slow thought processes, decrease concentration, inhibit activity, and disrupt short-term memory. The aim of this research is to determine the relationship between the incidence of hypertension and fulfilling the need for rest and sleep in the elderly in Buahdua village. The type of research is quantitative correlational with a cross sectional approach and survey method, using the PSQI (Pittsburgh Sleep Quality Index) questionnaire to determine the sleep quality of hypertension sufferers. The sampling technique used purposive sampling, calculations were carried out using the Slovin formula so that the sample used was 55 respondents. Data analysis used parametric statistical test, namely Pearson correlation analysis using SPSS software. Based on the data obtained, it was found that the average hypertension sufferer had systolic (54,5%) and diastolic (56,4%) in the mild hypertension category, the average elderly person with hypertension had adequate sleep wuality (60%). It can be concluded that there is a significant relationship between the incidence of hypertension and fulfilling the need for rest and sleep in the elderly in Buahdua village, both in systolic blood pressure and diastolic blood pressure. Therefore, elderly are expected to be able to know what causes poor sleep quality and as much as possible to avoid things that trigger sleep disorders.